TECHNOLOGIES USING 3D MODELING USING MODERN GRAPHIC SOFTWARE TOOLS (Conferencea, 2024)
3D modeling is one of the first steps in creating three-dimensional graphics. The concept of three-dimensional modeling means creating three-dimensional models of objects on a computer. A person who works with 3D models can be called a 3D artist or 3D modeler. A 3D model can also be rendered as a two-dimensional image through a process called 3D rendering, or used in computer simulations of physical phenomena. 3D models can be created automatically or manually.